Die morele verantwoordelikheid van internetdiensverskaffers: ‘n Christelik etiese perspektief - Britz, J. J. (Verbum et ecclesia, 2003)
The article deals with the moral responsibility of Internet Service Providers (ISPs) concerning the distribution of information in the virtual world, seen from the perspective of Christian Ethics. A number of case studies are discussed to illustrate some of the typical problems of responsibility experienced in this regard and the inadequacy of international legislation regulating internet services is pointed out. To adequately deal with specifically the moral responsibility of ISPs contemporary shifts in the concept of responsibility as a result of the process of modernisation are discussed. It is argued that the moral responsibility of ISPs is at least equivalent to that of other distributors of information. Nonetheless the moral responsibility ascribed to ISPs on the basis of liberal values would be different from that ascribed on the basis of Christian values. Liberals would tend to underplay the moral responsibility of ISPs to control the flow of information on the internet, while Christians would tend to emphasise their prospective responsibility to bar harmful information from the internet. However, in contemporary liberal democracies only ISPs serving Christians can be expected to exercise the moral responsibility that is regarded as ideal from a Christian perspective. From all ISPs the exercise of an optimal moral responsibility can nonetheless be expected.